Cerita Sabha Parwa NILAI-NILAI PENDIDIKAN MORAL DALAM CERITA SABHA PARWA PADA KISAH MAHABHARATA KARYA I GUSTI MADE WIDIA - Astuti, Kadek Dwi; Sanjaya, Putu; Prapnuwanti, Ni Luh Purnamasuari (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2025)
The story of Sabha Parwa was made in the form of a scientific literary work by I Gusti Made Widia, packaged with 17 subtitles of the story. Sabha Parwa is the second parwa of the Mahabharata story which in its story is related to the teachings of moral education values. The conflict of the story of sabha parwa tells the story of gambling or dice games and the harassment of women that occurred in the Kingdom of Hastinapur. This research aims to answer the following problems: (1) The structure of the Sabha Parwa story by I Gusti Made Widia; (2) The values of moral education in the story of Sabha Parwa and (3) The meaning contained in the story of Sabha Parwa by I Gusti Made Widia. The theories used are Literary Structural Theory, Value Theory and Semiotic Theory. The approach used in this study is the qualitative method of literature. Research results (1) The structure of the Sabha Parwa story from intrinsic elements, themes of struggle and moral conflict, there are 19 Sabha Parwa story characters, the setting of the main place of the kingdoms of Indraprasta and Hastinapura, the time setting is related to the time of the event, the setting of the atmosphere reflects the aspect of the atmosphere that occurred, the point of view using the first and third person and the storyline is advanced and there is also a flashback plot. The Extrinsic Element has moral, religious, and social educational value. (2) The values of moral education in the story of Sabha Parwa are; Religious, Respect, Sacrifice, Hard Work, Integrity, Self-Esteem and Dignity, and The Enemy Within. (3) There are two meanings of the Sabha Parwa story, namely denotative and connotative meanings. Of the 76 data, 41 data showed denotative meaning and 35 connotative meaning